2021
DOI: 10.33448/rsd-v10i6.15814
|View full text |Cite
|
Sign up to set email alerts
|

Rigor development and meat quality of Murrah buffalo from different production systems

Abstract: The purpose of this study was to evaluate the rigor mortis development and its effects on striploins quality of Murrah buffalos from meat (males) and dairy (females) productions. The rigor was monitored during carcass chilling (up to 22 h postmortem) and the meat physicochemical traits was accessed after 72 h postmortem. Glycolytic rate, measured by decreasing pH and glycogen content, was higher (p < 0.05) in female than in male buffalo, leading to a different onset rigor time (5-6 h and 9-10 h, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Lower pH values (p < 0.05) were observed for buffalo meat than for beef, but they were within the range considered normal for both buffalo (5.4-5.6) and cattle (5.5-5.8) [9]. Although [4] reported that the glycogen levels (74 to 106 mmol glucose equivalent/kg) of Murrah buffaloes immediately after slaughter were within the typical muscle glycogen reserve of well-fed and resting bovines, the lower pH observed in buffalo meat than cattle in this experiment suggests a higher postmortem glycolytic rate or less chronic stress during slaughter. Lower pH values for buffalo meat than beef were also reported by other authors [7,9,19], although [6] observed a higher pH value for buffalo meat and [20] did not observe differences between species.…”
Section: Quality Characteristicsmentioning
confidence: 65%
See 2 more Smart Citations
“…Lower pH values (p < 0.05) were observed for buffalo meat than for beef, but they were within the range considered normal for both buffalo (5.4-5.6) and cattle (5.5-5.8) [9]. Although [4] reported that the glycogen levels (74 to 106 mmol glucose equivalent/kg) of Murrah buffaloes immediately after slaughter were within the typical muscle glycogen reserve of well-fed and resting bovines, the lower pH observed in buffalo meat than cattle in this experiment suggests a higher postmortem glycolytic rate or less chronic stress during slaughter. Lower pH values for buffalo meat than beef were also reported by other authors [7,9,19], although [6] observed a higher pH value for buffalo meat and [20] did not observe differences between species.…”
Section: Quality Characteristicsmentioning
confidence: 65%
“…On the other hand, the buffalo herd is predominantly composed of animals of the Murrah, Mediterranean, Jafarabadi, and Carabao breeds. However, buffalo meat quality has not yet been well-studied due to the lack of carcass standardization [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil has the largest buffalo herd in the West, totaling 1.4 million animals (Instituto Brasileiro de Geografia e Estatística, 2019); however, the consumption of buffalo meat is still limited to some regions of the country. Buffalo meat is not well identified in part of Brazil due to its similarity with beef, as there are records that buffalo meat is marketed in two different ways: as buffalo meat, labeled as a high-quality (premium) meat; and sold as beef, when classified as having inferior quality (such as discarded females after the productive period) or when devalued in the producing region (Andrade et al, 2020;Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%